Understanding and analysis of online user inputs and behaviours - Tan, Lester Jia Yong (2017)
In the field of education of present, there has been a significant increase in the student body count as compared to the past. The enrolment rate is ever increasing due to the demands of having a proper education that the older generations never had. The increase in enrolment invoke a direct correlation to the amount of work a lecturer may have, and one such task affected by this correlation is the number of scripts one has to mark. Whereby teaching styles and methods remain consistent despite the student count, the process of marking involves more work for the lecturer with a larger number of students. This project aims to study and/or implement various methods of identifying keywords within text inputs as a basis for the grading of short answers. Natural Language Processing will also be researched on as marking of scripts involve dealing with human languages. And following the conclusion of the research phase, a grading program will be designed and implemented to assist lecturers with the marking of scripts.